Diagnostic Value of Combined Parameters for α-Thalassemia-1 Screening in Pregnant Women - Tangvarasittichai, Orathai; Jeenapongsa, Rattima; Sitthiworanan, Chanthonrat; Sanguansermsri, Torpong (Asian Health, Science and Technology Reports, 2004)
Hb Bart’s hydrops fetalis, the most severe case α-thalassemia, can be prevented with an early effective diagnosis of α-thalassemia-1 carrier pregnant women. Current commonly used diagnostic parameter is MCV or OFT. However both tests are not specific enough. Therefore, more samples are required further tests. This study aimed to investigate a parameter or combined parameters that provide(s) higher specificity and sensitivity in differential diagnosis between carriers and non-carriers of α-thalassemia-1. Blood samples were collected from 1,000 pregnant women attending an antenatal clinic, Buddhachinaraj Hospital, Phitsanulok. The EDTA anticoagulated blood was subjected to determination of RBC count, RBC indices (Hb, Hct, MCH, MCHC, MCV and RDW) by an automated blood cell analyzer, OFT and DNA extraction for PCR-based assay. Data were analyzed by ROC curves and discriminant analysis and then compared with Student’s t-test. This study showed that combined parameters revealed more effective diagnosis of α-thalassemia-1 than a single parameter. Considering 100% sensitivity, the most effective combination indicator was MCH/OFT/RDW (92.4% specificity), followed by MCH/OFT/MCV (91.9% specificity), MCH/OFT (91.7% specificity), MCH/RDW/MCV (90.0% specificity), MCH/ RDW (89.6% specificity) and MCH/MCV (88.5% specificity). MCH, MCV and OFT used as a single parameter exhibited % specificity of 87.3, 82.4 and 81.7%, respectively. The cut-off points of these parameters were as followed: MCH (≤ 25 pg), MCV (≤ 75 fL), RDW (≥ 14.5%) and OFT (≤ 55%). The results suggested that the parameter combinations provide better predictive values of a positive test for α-thalassemia-1 carriers with no false negative. The best combined parameter was MCH/OFT/RDW.